2023
DOI: 10.1101/2023.07.26.550642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent plasticity of a highly specific olfactory circuit inDrosophila melanogaster

Abstract: Drosophila melanogaster encounters a variety of odor cues signaling potentially harmful threats throughout its life, which are detected by highly specialized olfactory circuits enabling the animal to avoid them. We studied whether such crucial neuronal pathways are hard-wired or can be modulated by experience. Using long-term exposure to high concentrations of geosmin, an indicator of potentially lethal microorganisms, we demonstrate at the single-cell level that the underlying neuronal circuitry undergoes str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In Drosophila, feedback loops have been described between the MB and the AL [96]. Although the PNs did not show structural plasticity in their axonal projections to the LH and MB following chronic exposure during the critical period [20], we cannot rule out functional plasticity within other LH or MB neurons. Additionally, it is not known if functional LH or MB circuits are required for the expression of CPP in the AL.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In Drosophila, feedback loops have been described between the MB and the AL [96]. Although the PNs did not show structural plasticity in their axonal projections to the LH and MB following chronic exposure during the critical period [20], we cannot rule out functional plasticity within other LH or MB neurons. Additionally, it is not known if functional LH or MB circuits are required for the expression of CPP in the AL.…”
Section: Discussionmentioning
confidence: 68%
“…This time of heightened neuronal plasticity is called the critical period and was first defined by the Nobel prize-winning work of Hubel and Wiesel in 1962 in the context of the development of cortical receptive fields of binocular vision [1][2][3][4][5]. Since then, critical periods have been discovered in multiple sensory modalities across species [6][7][8], including the visual, auditory, somatosensory, and olfactory cortices of mice [9][10][11][12] as well as the visual and sensorimotor circuits [13,14] of the fruit fly larvae and in the olfactory system of adult flies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Experience-dependent plasticity can occur both during and after the critical period.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in volume can be attributed to the increase in PN and LN arborizations in an odor specific manner. 1921,27 A specific subpopulation of GABAergic LNs, the LN1 neurons, the adenylate cyclase rutabaga increases cAMP levels to promote CREB dependent gene transcription. This facilitates the structural plasticity observed in both the LNs and PNs.…”
Section: Discussionmentioning
confidence: 99%
“…At the circuit level, the structural plasticity resulting in an increase in glomerular volume is manifested through an increase in the number of LN and PN arbors innervating the glomerulus while the total number of neurons remains intact. 1921,27 Glomerular volume decrease, on the other hand is caused by retraction of the OSN axon fibers upon chronic ethyl butyrate exposure in a specific glomerulus. 23 These studies demonstrated that the olfactory CPP in Drosophila shares many of the same molecular mechanisms as visual CPPs.…”
Section: Introductionmentioning
confidence: 99%